Treatment of Iatrogenic Parasitic Leiomyoma as a Rare Complication of Myomectomy Using a Morcellator: A Clinical Case (Perioperaciina Medicina, 2026)
Introduction: Parasitic leiomyomas (PL) are a rare iatrogenic complication that most commonly occurs after laparoscopic myomectomy or hysterectomy using an electromechanical morcellator without the use of an endocontainer. Dispersion of myometrial fragments during morcellation can lead to their implantation and growth on the peritoneum, creating diagnostic and therapeutic challenges.Case Presentation: We present the case of a 41-year-old patient who sought further treatment 10 years after laparoscopic myomectomy with morcellation. The patient’s history included anemia due to myoma growth. Preoperative diagnosis in 2025 using MRI confirmed the presence of multiple intramural and subserous uterine leiomyomas (FIGO 4, 5, 6), as well as approximately 15 extra-organ solid formations characteristic of extrauterine parasitic leiomyomas (FIGO 8). A combined surgical intervention was performed: laparoscopic excision of parasitic myomas followed by conversion to laparotomy for conservative myomectomy. Histological examination confirmed the diagnosis of leiomyoma.Conclusions: This case highlights the importance of thorough diagnosis in patients with pelvic masses in their history, especially after surgeries involving morcellation. MRI is a highly informative method for differential diagnosis. Combined laparoscopic and laparotomic access may be an effective strategy for treating such complex cases. The main emphasis should be on prevention through strict adherence to safe morcellation techniques in endocontainers
Keywords: parasitic myoma; leiomyoma; laparoscopy; laparotomy; morcellation; pelvic pain; iatrogenic complication; patient safety